Analysis Of Slang Words In Youtube Comments On The 2024 Indonesian Presidential And Vice Presidential Candidate Debate - Via Delfia Br Karo; I Nyoman Adi Jaya Putra; I Wayan Swandana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes slang words found in the YouTube comment sections related to the 2024 Indonesian presidential and vice-presidential debates. The purpose of this research is to identify the types, meanings, and functions of slang words used by YouTube users. This study employs a descriptive qualitative method with a non-participant observation technique, using data from five debate videos on the Najwa Shihab YouTube channel, selected based on topic relevance and high audience engagement. The types of slang were classified using Allan and Burridge’s (2006) theory, while their functions were analyzed based on Jakobson’s theory (in Soeparno, 2002) and Partridge’s theory (in Martinus, 2018). The findings reveal a total of 51 slang words divided into five types: Imitative (28 items/50%), Acronym (9 items/17.65%), Fresh and Creative (9 items/16.07%), Clipping (3 items/5.36%), and Flippant (2 items/3.57%), with Imitative being the most dominant. In terms of function, nine functions of slang were identified: emotive, conative, referential, phatic, poetic/humor, social identity, secretive, economic, and attracting attention, with the emotive function being the most dominant. These findings indicate that slang plays an important role in shaping digital communication and political discourse within Indonesia’s online communities.